Le mentorat en début de carrière : retombées sur la charge professorale et conditions de mise en œuvre d'un programme en milieu universitaire - Paul-Armand Bernatchez; Sylvie C. Cartier; Marilou Bélisle; Claire Bélanger
This review of the literature was carried out in order to assess the impact of mentoring in educational settings and in particular mentoring addressing faculty in early stages of their academic career and the necessary requirements for implementing programmes. The main issues raised by our study indicate that as far as informal mentoring and formal mentoring are concerned there is no definite answer regarding the efficiency of one over the other. Furthermore despite contrasted views in the literature, it seems that mentoring does have a positive impact on professional development of early stage academics for most of the components of their professorial function including teaching. Last of all experiences carried out in various institutions allowed us to examine implementation and practise in mentoring and to devise a framework comprising three steps.